An isolated capitellum fracture of the humerus in adult: A rare case report - Shah Kalawar, Rosan Prasad; Chaudhary, P; Maharjan, R; Afaque, SF (Health Renaissance, 2017)
Introduction: Isolated capitellum fractures are rare and represent only 1% of all elbow fractures and 6% of distal humeral fractures. Case description: A 45-year-old right hand dominant female presented to us with pain and stiffness in her left elbow following a fall onto the outstretched hand that occurred 6 months prior. She had capitellum fracture with avascular changes and excision of the fractured fragment was done. Physiotherapy was initiated with outcome of nearly normal elbow function. At the time of injury, she was unable to move her elbow actively due to pain and she was misdiagnosed as soft tissue injury earlier in a local hospital. Conclusion: Possibility of rare diagnosis such as capitellum fracture should also be kept in mind while treating elbow injuries. Health Renaissance 2015; 13 (1): 112-116